Humans vs Animals: Distinctive Viewpoints on Love and the Ethical Implications in Greyfriars Bobby - Rifani, Reysha Aqila (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
This study analyzes the correlation between the human-animal relationship and the ethicalimplications represented in Eleanor Atkinson’s Greyfriars Bobby. It aims to elaborate on thehuman viewpoint of “love” in the novel which affects the way they act towards animals. Bobbyis a dog who catches the town’s attention for his display of grief over his owner, Auld Jock whodied of pneumonia. He becomes the symbol of fidelity and affection for his effort to be on AuldJock’s side forever. The moral-philosophical approach is used to examine the moral content ofthe novel thoroughly. A qualitative method is also employed to discuss the findings the writerfound in the novel. The findings indicate that the link between humans and animals in terms ofemotional attachment contributes to the way humans give affection, which often results in anemerging sense of responsibility to look out for each other’s well-being and prosperity.